Situation Report: Romania, 6 February 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Rejects Soviet-Style Reform, Enforces Austerity Policy / by Anneli Ute Gabanyi Workers' Protests Flaring Up / by Anneli Ute Gabanyi Social Hardships Reflected in CMEA Statistics / by Vladimir Socor Hidden Unemployment Seems Set to Rise / by Carmen Pompey More about Abortions / by Dan Ionescu National Peasant Group Silenced after Human Rights Initiative / by Vladimir Socor Ceausescu's Personality Cult - An Analysis / by Anneli Ute Gabanyi Santa Claus Comes over Once a Year - Or Not at All? / by Crisula Stefanescu